PMMA heat-conducting composite material based on three-dimensional heterojunction heat-conducting framework C-BN and bulk polymerization preparation method of PMMA heat-conducting composite material

The f-BNNS@C-BN/PMMA composite material was prepared through bulk polymerization process, which solved the problems of uneven filler dispersion and large interface thermal resistance in traditional polymer-based thermal conductive composite materials, and achieved synergistic enhancement of efficient thermal conductivity and mechanical properties.

CN120795520APending Publication Date: 2025-10-17ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511273763.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

In traditional polymer-based thermally conductive composite materials, the fillers are unevenly dispersed and the interface thermal resistance is large, making it difficult to meet the needs of efficient directional heat dissipation. In addition, the vacuum infusion process is prone to form bubbles and voids, which reduces the thermal conductivity and mechanical properties.

Method used

The bulk polymerization process was used to infuse a three-dimensional thermal conductive skeleton with a low-viscosity prepolymer. The f-BNNS@C-BN/PMMA composite material was prepared through in-situ polymerization to form a non-covalent and covalent synergistic effect, thereby reducing the interfacial thermal resistance and enhancing the mechanical properties.

Benefits of technology

The efficient thermal conductivity of the composite material was improved, with the in-plane and out-of-plane thermal conductivities reaching 0.45 W/(mK) and 1.20 W/(mK) respectively, the tensile strength reaching 35.60 MPa, and the compressive stress reaching 100.30 MPa, significantly improving the thermal conductivity and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795520A_ABST
    Figure CN120795520A_ABST
Patent Text Reader

Abstract

The invention discloses a PMMA (polymethyl methacrylate) heat-conducting composite material based on a three-dimensional heterojunction heat-conducting framework C-BN (boron nitride) and a bulk polymerization preparation method thereof. The preparation method comprises the following steps: firstly, preparing a BN / PUF foam sacrificial template with proper pore size and uniform distribution through an in-situ polymerization foaming process, and performing high-temperature carbonization to form a three-dimensional orderly distributed heat-conducting skeleton C-BN; the preparation method comprises the following steps: uniformly dispersing 1-vinyl-3-methylimidazole iodized salt functionalized BN nanosheets into an MMA monomer to prepare a BNNS / PMMA pre-polymerized solution, pouring the BNNS / PMMA pre-polymerized solution into a three-dimensional heat-conducting skeleton which is impregnated and modified by an ionic liquid, and curing to obtain the heat-conducting composite material f-BNNS (at) C-BN / PMMA which is obviously improved in the vertical direction and the horizontal direction. According to the invention, through modification of the three-dimensional heat-conducting skeleton and combination of a step-by-step bulk polymerization pouring process, the interface action between the three-dimensional heat-conducting skeleton and a polymer matrix is significantly improved, and the interface thermal resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of polymer heat-conducting composite materials, and particularly relates to a PMMA heat-conducting composite material based on a three-dimensional heterojunction heat-conducting framework C-BN and a bulk polymerization preparation method thereof. BACKGROUND

[0002] With the development of electronic devices towards high power density, miniaturization and integration, the heat dissipation problem has become a key bottleneck restricting the performance and reliability. The traditional polymer-based heat-conducting composite material is difficult to meet the demand of high-efficiency directional heat dissipation due to problems such as uneven dispersion of fillers and high interfacial thermal resistance. In recent years, the innovative design of the three-dimensional heterojunction heat-conducting framework structure provides a solution to break through the heat management bottleneck of the traditional polymer-based composite material. The multi-scale structure design of the three-dimensional heat-conducting path forms an efficient "phonon highway" through the directional arrangement of fillers, significantly reduces the interfacial thermal resistance between fillers, and improves the heat conduction efficiency of the composite material, providing a new preparation method for heat dissipation of high-power electronic devices.

[0003] Most of the polymer heat-conducting composite materials based on the three-dimensional porous heat-conducting framework reported in the literature at present adopt the vacuum infusion process, and the polymer matrix is mostly epoxy resin, silicone resin and the like. However, in the infusion process, the high-viscosity resin often has the following disadvantages: bubbles, pores and voids are easily formed at the interface between the framework and the matrix, the interfacial bonding between the three-dimensional framework and the polymer matrix is weak, which significantly increases the phonon scattering, thereby reducing the overall heat conduction performance and mechanical properties. SUMMARY

[0004] The present application provides a PMMA heat-conducting composite material based on a three-dimensional heterojunction heat-conducting framework C-BN and a bulk polymerization preparation method thereof, aiming at the deficiencies of the prior art. The present application uses a three-dimensional porous heat-conducting framework as a template, and regulates the interfacial thermal resistance of the composite material based on the chemical covalent bond formed by free radical copolymerization and the cation-π non-covalent synergistic mechanism, to prepare a polymethyl methacrylate heat-conducting composite material. In the preparation process, the present application adopts a bulk polymerization step infusion process, infuses the three-dimensional heat-conducting framework with a low-viscosity prepolymer, efficiently fills the small gaps, and realizes the non-covalent and covalent synergistic effect between the polymer and the heat-conducting framework through in-situ bulk polymerization, thereby reducing the interfacial thermal resistance and realizing the synergistic enhancement of the heat conduction and mechanical properties.

[0005] The f-BNNS@C-BN / PMMA composite material is prepared by using the bulk in-situ polymerization process, first, a BN / PUF foam sacrificial template with appropriate pore size and uniform distribution is prepared by the in-situ polymerization foaming process, and a three-dimensional skeleton C-BN is formed after high-temperature carbonization; then, the three-dimensional heat-conducting skeleton is functionalized by using 1-vinyl-3-methyl imidazole iodine salt, and the v-IL@BNNS / PMMA prepolymer liquid is perfused, and the f-BNNS@C-BN / PMMA heat-conducting composite material with a low thermal resistance interface structure is prepared by in-situ polymerization.

[0006] The method for preparing the PMMA heat-conducting composite material based on the three-dimensional porous heterojunction heat-conducting skeleton C-BN by using the bulk polymerization process, comprising the following steps:

[0007] Step 1: preparation of modified C-BN three-dimensional porous heat-conducting skeleton

[0008] 1a, h-BN is added to polyurethane A material, and stirred until h-BN is uniformly mixed, then B material is quickly added to the above mixture, and quickly stirred uniformly at 1800 rpm, and foamed after standing, which is recorded as BN / PUF foam composite material (BN / PUF foam sacrificial template).

[0009] 1b, the BN / PUF foam composite material is cut into the required size (3*3*2.5 cm), and is placed vertically along the original foaming direction in a ceramic capsule, and is placed in a tube furnace, and is heated to 800 DEG C at a heating rate of 5 DEG C / min under an argon atmosphere, and is kept for 60 minutes, so that the polyurethane foam is fully carbonized to form a C-BN three-dimensional porous heterojunction heat-conducting skeleton.

[0010] 1c, 1-vinyl-3-methyl imidazole iodine salt ionic liquid is heated to a molten state (80 DEG C), and then the C-BN three-dimensional porous heterojunction heat-conducting skeleton is hung in the molten ionic liquid, and is completely immersed, and is magnetically stirred at 80 DEG C for 12 hours, and then is placed in a vacuum drying box and immersed at 30 DEG C for 24 hours to obtain the ionic liquid modified C-BN three-dimensional porous heterojunction heat-conducting skeleton.

[0011] In this step, the formula of the foam template and the process of sintering the three-dimensional skeleton will affect the stability of the skeleton. If not properly controlled, the skeleton will collapse during sintering and cannot form a uniform porous structure.

[0012] Step 2: preparation of modified BNNS

[0013] 2a, 1.50 g of h-BN powder (10 μm in diameter), 0.60 g of zirconia spherical beads with a diameter of 0.20 mm and 0.60 g of zirconia spherical beads with a diameter of 0.30 mm, 400 mL of deionized water were placed in a 500 mL solvent bottle, and ultrasonic treatment was performed at room temperature for 48 h. After centrifugation at 3000 rpm for 10 min, the upper liquid was taken, and then centrifugation was performed at 12000 rpm for 10 min, and the lower solid was taken. The obtained product was placed in a 60 ℃ oven for 24 h to obtain boron nitride nanosheets (BNNS).

[0014] 2b, 0.50 g of BNNS was added to 100 mL of an aqueous ionic liquid solution, and ultrasonic stirring was performed for 12 h. The treated mixture was ball milled at a speed of 500 rpm for 8 h, and then freeze-drying was performed after suction filtration to obtain ionic liquid modified BNNS powder.

[0015] Step 3: Preparation of f-BNNS@C-BN / PMMA thermally conductive composite material

[0016] 0.20 g of ionic liquid modified BNNS powder (2 wt% of MMA monomer) was added to 5 g of THF and stirred and ultrasonically treated for 24 h until uniformly dispersed. 10 g of monomer MMA, 0.04 g of initiator AIBN and ionic liquid modified BNNS powder were weighed and mixed, and a pre-polymerization reaction was performed at 80℃ under magnetic stirring. When the viscosity of the reaction system was glycerol-like (900-1500 mPa·s), heating was stopped. The pre-polymer solution was slowly added to the modified C-BN three-dimensional porous heterojunction thermally conductive framework obtained in step 1 after cooling and standing. The sample filled with the pre-polymer solution was placed in an oven for gradient heating until hardening (40℃ for 2 hours, 50℃ for 2 hours, 60℃ for 2 hours), and then the temperature was increased to 100-110℃ for 1 h for curing to obtain the f-BNNS@C-BN / PMMA thermally conductive composite material.

[0017] In this step, the conversion rate control of the pre-polymerization step is a more important factor. If the conversion rate control of the pre-polymerization step is not good, the template after filling will be deformed or even collapsed due to the shrinkage of PMMA polymerization. The conversion rate is controlled at about 10-20%. If the viscosity is too large, more than 1500 mPa·s, the liquid flowability is poor, and it is difficult to effectively fill the pores of the thermally conductive framework; and if the viscosity is too small, less than 900 mPa·s, on the one hand, BNNS cannot be effectively and stably dispersed, and on the other hand, the shrinkage rate of MMA after polymerization is large, which leads to deformation or even collapse of the framework. Figure 7 A physical diagram showing that BNNS cannot be effectively and stably dispersed when the conversion rate is less than 10% is provided.

[0018] In step 1, the polyurethane A material comprises the following components by mass fraction: polyether polyol 330N (73.9 parts), ethylene glycol (8 parts), combined polyol POP36 / 28 (10 parts), amine catalyst (one or more of A-300, DMEA, ADPA) 1 part, water 0.8 parts, HFC-245fa blowing agent 6 parts, DC-3043 silicone oil 0.3 parts. The B material is polymethylene polyisocyanate 48.2 parts.

[0019] In step 1, h-BN accounts for 2-15 wt% of the total mass of A material and B material, such as 2 wt%, 6 wt%, 10 wt%, 14 wt%, preferably 10 wt%, because it can improve the thermal conductivity while ensuring uniform cell size and uniform distribution of the PU template.

[0020] In step 2b, the concentration of the ionic liquid aqueous solution is 2-8 wt%. The ionic liquid is one or more of 1-vinyl-3-methylimidazole iodide (v-IL), 1-vinyl-3-butyl imidazole tetrafluoroborate (v-IL), 1-allyl-3-methylimidazole chloride, dimethylaminoethyl methacrylate quaternary ammonium salt, and acryloyloxyethyl trimethylammonium chloride. Ionic liquids containing double bonds such as vinyl or allyl-imidazole iodide (bromide) can participate in copolymerization with methyl methacrylate. At the same time, imidazolium salt is a non-metallic ion with positive charge, which can form cation-π interaction with BN, reduce the interfacial thermal resistance, and thus improve the mechanical properties and thermal conductivity of the composite material.

[0021] In step 3, the mass of the ionic liquid modified BNNS powder accounts for 0.5-5 wt% of the mass of the MMA monomer.

[0022] In step 3, the modified C-BN three-dimensional porous heterojunction thermal skeleton accounts for 9-27 wt% of the total mass of the composite material. Within this range, the more the filler content, the more the horizontal and vertical thermal conductivity of the composite material will increase to varying degrees, the Young's modulus and compressive strength will increase, but the tensile strength and elongation at break will decrease.

[0023] The present application modifies the three-dimensional thermal skeleton C-BN and boron nitride nanosheet by using imidazole ionic liquid with double bonds in the side chain, and prepares PMMA-based thermal conductive composite material based on bulk polymerization process. The functionalized filler, thermal skeleton and monomer are in-situ polymerized, forming a synergistic effect of cation-π non-covalent interaction and C-C chemical covalent connection between the polymer and the thermal skeleton, which significantly improves the mechanical properties of the composite material while improving the horizontal and vertical thermal conductivity of the composite material.

[0024] The beneficial effects of the present application are as follows:

[0025] The present application utilizes in-situ foaming process to prepare BN / PUF foam template with appropriate pore size and uniform distribution, and high-temperature carbonization to form porous C-BN heterojunction three-dimensional heat-conducting skeleton; and adopts bulk polymerization to prepare polymethyl methacrylate-based heat-conducting composite material. The three-dimensional heat-conducting network is constructed by ion liquid modification of the C-BN skeleton and auxiliary addition of v-IL@BNNS, and the cation-π non-covalent interaction and C-C chemical covalent connection between the fillers and PMMA macromolecules are formed to enhance the interface action of the fillers and the matrix and reduce the interface thermal resistance. The f-BNNS@C-BN / PMMA heat-conducting composite material with a filler content of 10.30 wt% is prepared, and the in-plane and out-of-plane thermal conductivities reach 0.45 W / (mK) and 1.20 W / (mK), respectively, and the heat-conducting enhancement efficiency of the composite material relative to pure PMMA reaches 221.40% and 252.94%, respectively. In addition, the composite material also has the characteristics of light weight, high strength and excellent mechanical ability, and the tensile strength reaches 35.60 MPa, and the compression stress under 50% strain can reach 100.30 MPa. BRIEF DESCRIPTION OF DRAWINGS

[0026] Figure 1 It is the preparation flowchart of the f-BNNS@C-BN / PMMA heat-conducting composite material of the present application embodiment 1.

[0027] Figure 2 It is the scanning electron microscope planar view of the h-BN (a), BNNS (b) and v-IL@BNNS (c) fillers of the present application embodiment 1.

[0028] Figure 3 It is the scanning electron microscope section view of the f-BNNS@C-BN / PMMA composite material of the present application embodiment 1. Wherein (a), (b) are different magnifications.

[0029] Figure 4 It is the thermal conductivity graph of the sample obtained in the present application embodiment 1.

[0030] Figure 5 It is the compression strain curve and stress-strain curve of the BNNS@C-BN / PMMA and f-BNNS@C-BN / PMMA of the present application embodiment 1. Fig. a is the compression strain curve of the BNNS@C-BN / PMMA and f-BNNS@C-BN / PMMA; Fig. b is the stress-strain curve of the BNNS@C-BN / PMMA and f-BNNS@C-BN / PMMA

[0031] Figure 6 It is the real object graph of the collapsed skeleton obtained in the present application embodiment 2.

[0032] Figure 7 It is the real object graph obtained when the conversion rate is less than 10% in the present application embodiment 3.

[0033] Figure 8 BN / PUF scanning electron microscope images of different BN contents of Example 4 of the present application, (a)-(e) are different BN contents, respectively. DETAILED DESCRIPTION

[0034] The following detailed description of the embodiments of the present application is based on the premise of the technical solutions of the present application, and detailed implementation and specific operation processes are given, but the protection scope of the present application is not limited to the following examples.

[0035] The boron nitride / polyurethane foam sacrificial template formula used in the example is shown in the following table:

[0036]

[0037] In the following examples, the thermal conductivity is measured by a thermal conductivity tester (Hot Disk, Kaiguanasi Instrument Trading Shanghai Co., Ltd.).

[0038] Example 1:

[0039] This example is prepared according to the following steps:

[0040] Step 1: Preparation of BN / PUF foam sacrificial template

[0041] 27 g of polyurethane A material, 13 g of B material polymethylene polyisocyanate, and 4.4 g of hexagonal boron nitride h-BN were weighed. The h-BN was added to the A material and stirred to mix evenly, then the B material was quickly added to the above solution, and after rapid stirring at 1800 rpm, the foam was placed, and was recorded as BN / PUF foam sacrificial template.

[0042] Step 2: Preparation and modification of C-BN three-dimensional thermal conductive skeleton

[0043] The BN / PUF foam was cut into 3x3x2.5 cm size, and was placed vertically along the original foaming direction in a ceramic square boat, and was placed in a tube furnace, and was heated to 800℃ at a heating rate of 5℃ / min under argon atmosphere, and was kept for 60 minutes, so that the polyurethane foam was fully carbonized to form a C-BN three-dimensional porous heterojunction thermal conductive skeleton; then the C-BN skeleton was immersed in molten v-IL ionic liquid, completely immersed, and was stirred at 80℃ for 12h, and then was placed in a vacuum oven at 30℃ for 24h, to obtain an ionic liquid modified C-BN three-dimensional porous heterojunction thermal conductive skeleton.

[0044] Step 3: Preparation of boron nitride nanosheet BNNS by h-BN exfoliation

[0045] h-BN was exfoliated by ultrasonic exfoliation method. 1.50 g of h-BN powder, 0.60 g of zirconia ball milling beads with a diameter of 0.20 mm and 0.60 g of zirconia ball milling beads with a diameter of 0.30 mm, and 400 mL of deionized water were placed in a 500 mL solvent bottle, and ultrasonic exfoliation was carried out at room temperature for 48 h. After centrifugation at 3000 rpm for 10 min, the upper liquid was taken, and then centrifugation was carried out at 12000 rpm for 10 min, and the lower solid was taken. The obtained product was placed in a 60 ℃ oven for 24 h to obtain boron nitride nanosheets (BNNS).

[0046] Step 4: Preparation of ion liquid modified boron nitride nanosheets v-IL@BNNS

[0047] 0.50 g of BNNS was added to 100 mL of 1-vinyl-3-methylimidazole iodine salt (v-IL) aqueous solution with a concentration of 4 wt%, and ultrasonic stirring was carried out for 12 h. The treated mixture was poured into a ball mill tank, and different sizes of agate zirconia balls were added to the ball mill tank at a fixed weight ratio. After mixing at a speed of 500 rpm for 8 h, v-IL@BNNS solution was obtained. After suction filtration, water washing and freeze drying, v-IL@BNNS powder was obtained.

[0048] Step 5: Preparation of PMMA prepolymer:

[0049] 0.20 g of v-IL@BNNS and 5 g of THF were placed in a 20 mL black glass bottle and stirred and ultrasonically dispersed for 24 h. 10 g of monomer MMA, 0.04 g of initiator AIBN and v-IL@BNNS were weighed and mixed, and pre-polymerization was carried out at 80 ℃ under magnetic stirring. When the viscosity of the reaction system was glycerol-like, heating was stopped.

[0050] Step 6: Preparation of f-BNNS@C-BN / PMMA composite material

[0051] The above prepolymer solution was slowly added to the modified C-BN three-dimensional porous heterojunction heat conducting skeleton after slight cooling. The sample filled with the prepolymer solution was placed in an oven with gradient heating until hardening (40 ℃ for 2 h, 50 ℃ for 2 h, and 60 ℃ for 2 h). After hardening, the temperature was increased to 100-110 ℃ for 1 h to make the reaction complete, and a f-BNNS@C-BN / PMMA heat conducting composite material was obtained.

[0052] Example 2:

[0053] The C-BN skeleton was prepared according to the following steps:

[0054] Step 1:

[0055] Take 27 g of polyurethane A material, 13 g of B material polymethylene polyisocyanate, 4.4 g of hexagonal boron nitride h-BN. Add h-BN to A material and mix evenly, then quickly add B material to the above solution, stir quickly at 1800 rpm, then stand and foam, marked as BN / PUF foam sacrificial template.

[0056] Step 2:

[0057] Cut the BN / PUF foam into a size of 3x3x2.5 cm, place it vertically along the original foaming direction in a ceramic capsule, and place it in a tube furnace under an argon atmosphere. First, heat it to 220°C at a rate of 0.3°C / min, then increase the temperature to 900°C at a rate of 1°C / min, and keep it at this temperature for 150 min to achieve complete reaction, forming a C-BN three-dimensional porous heterojunction heat-conducting skeleton which will be broken.

[0058] Example 3:

[0059] This example is prepared as follows to prepare f-BNNS@C-BN / PMMA composite material:

[0060] Step 1: Preparation of BN / PUF foam sacrificial template

[0061] Take 27 g of polyurethane A material, 13 g of B material polymethylene polyisocyanate, 4.4 g of hexagonal boron nitride h-BN. Add h-BN to A material and mix evenly, then quickly add B material to the above solution, stir quickly at 1800 rpm, then stand and foam, marked as BN / PUF foam sacrificial template.

[0062] Step 2: Preparation and modification of C-BN three-dimensional heat-conducting skeleton

[0063] Cut the BN / PUF foam into a size of 3x3x2.5 cm, place it vertically along the original foaming direction in a ceramic capsule, and place it in a tube furnace under an argon atmosphere. First, heat it to 220°C at a rate of 0.3°C / min, then increase the temperature to 900°C at a rate of 1°C / min, and keep it at this temperature for 150 min to achieve complete reaction, forming a C-BN three-dimensional porous heterojunction heat-conducting skeleton which will be broken.

[0064] Step 3: Preparation of boron nitride nanosheets BNNS by exfoliation of h-BN

[0065] h-BN was exfoliated by ultrasonic exfoliation method. 1.50 g of h-BN powder, 0.60 g of zirconia milling beads with a diameter of 0.20 mm and 0.60 g of zirconia milling beads with a diameter of 0.30 mm, and 400 mL of deionized water were placed in a 500 mL solvent bottle, and ultrasonic exfoliation was carried out at room temperature for 48 h. After centrifugation at 3000 rpm for 10 min, the upper liquid was taken, and then centrifugation was carried out at 12000 rpm for 10 min, and the lower solid was taken. The obtained product was placed in a 60 ℃ oven for 24 h to obtain boron nitride nanosheets (BNNS).

[0066] Step 4: Preparation of ion liquid modified boron nitride nanosheet v-IL@BNNS

[0067] 0.50 g of BNNS was added to 100 mL of 1-vinyl-3-methylimidazole iodine salt (v-IL) aqueous solution with a concentration of 4 wt%, and ultrasonic and stirring were carried out for 12 h. The treated mixture was poured into a ball mill tank, and different sizes of agate zirconia balls were added to the ball mill tank at a fixed weight ratio. After mixing at a speed of 500 rpm for 8 h, v-IL@BNNS solution was obtained. After suction filtration, water washing and freeze drying, v-IL@BNNS powder was obtained.

[0068] Step 5: Preparation of PMMA prepolymer:

[0069] 0.20 g of v-IL@BNNS and 5 g of THF were placed in a 20 mL black glass bottle and stirred and ultrasonically dispersed for 24 h. 10 g of monomer MMA, 0.04 g of initiator AIBN and v-IL@BNNS were weighed and mixed, and pre-polymerization was carried out at 80 ℃ under magnetic stirring. After about 15 minutes, the heating was stopped, and at this time the conversion rate of the polymerization reaction was less than 10%. In the following comparative example, the pre-polymerization was generally carried out for about 25 minutes for infusion.

[0070] Step 6: Preparation of f-BNNS@C-BN / PMMA composite material

[0071] The above pre-polymer solution was slowly added to the ion liquid modified C-BN three-dimensional framework after being slightly cooled. The sample infused with the pre-polymer solution was placed in an oven with gradient heating until it hardened (40 ℃ for 2 hours, 50 ℃ for 2 hours, and 60 ℃ for 2 hours). After hardening, the temperature was raised to 100-110 ℃ for 1 h to make the reaction tend to be complete, and f-BNNS@C-BN / PMMA composite material was obtained.

[0072] Due to the low conversion rate of the prepolymer, BNNS settled during the polymerization process, and the system after infusion showed stratification, as shown in Figure 7 .

[0073] Example 4:

[0074] This example was prepared according to the following steps to prepare BN / PUF:

[0075] Take 27 g of polyurethane A material, 13 g of B material polymethylene polyisocyanate, hexagonal boron nitride h-BN (0 wt%, 2 wt%, 6 wt%, 10 wt%, 14 wt%). Add h-BN to A material and stir until mixed evenly, then quickly add B material to the above solution, stir quickly at 1800 rpm, then let it stand and foam, and record it as BN / PUF foam sacrificial template.

[0076] Comparative Example 1:

[0077] This comparative example was prepared according to the following steps to prepare BNNS@C-BN / PMMA composite material:

[0078] Step 1: Preparation of C-BN skeleton

[0079] Take 27 g of polyurethane A material, 13 g of B material isocyanate, 4.4 g of h-BN. Add h-BN to a paper cup containing A material, stir with a glass rod until h-BN is mixed evenly, then quickly add B material to the above solution and use a stirrer to stir quickly at 1800 rpm until the bottom of the paper cup is heated. After stirring is completed, place it on the desktop and let it stand and foam, and record it as BN / PUF, which is carbonized at high temperature to form a C-BN three-dimensional skeleton.

[0080] Step 2: Preparation of BNNS

[0081] h-BN was exfoliated by ultrasonic exfoliation method. 1.50 g of h-BN powder, 0.60 g of zirconium oxide ball milling beads with a diameter of 0.20 mm and 0.60 g of zirconium oxide ball milling beads with a diameter of 0.30 mm, and 400 mL of deionized water were placed in a 500 mL solvent bottle, and ultrasonic exfoliation was carried out at room temperature for 48 h. The exfoliation was carried out at a speed of 3000 rpm and 12000 rpm, respectively, for 10 min each time. The upper layer liquid was taken for the former, and the lower solid was taken for the latter. The product was placed in a 60 ℃ oven for 24 h, and finally obtained boron nitride nanosheet (BNNS) material.

[0082] Step 3: Preparation of BNNS@C-BN / PMMA composite material

[0083] Put 0.20 g BNNS, 5 g THF into a 20 mL black glass bottle, stir and ultrasonic for 24 h until evenly dispersed. Weigh 10 g monomer MMA, 0.04 g initiator AIBN and BNNS, mix well, and pre-polymerize at 80 ℃ under magnetic stirring. When the reaction system is slightly viscous, stop heating, then slowly drop the above pre-polymer solution into the C-BN three-dimensional skeleton after slightly cooling. Put the sample filled with pre-polymer solution into a 50 ℃ oven for 2-3 days until hardening, then heat to 100-115 ℃ for 1 h to make the reaction complete, and obtain BNNS@C-BN / PMMA composite material.

[0084] Comparative Example 2:

[0085] The comparative example is prepared according to the following steps to prepare polymethyl methacrylate (PMMA):

[0086] Weigh 10 g monomer MMA, 0.04 g initiator AIBN and mix well, and pre-polymerize at 60 ℃ under magnetic stirring. When the reaction system is slightly viscous, stop heating, then slowly drop the above pre-polymer solution into the C-BN three-dimensional skeleton after slightly cooling. Put the sample filled with pre-polymer solution into a 50 ℃ oven for 2-3 days until hardening, then heat to 100-115 ℃ for 1 h to obtain PMMA.

[0087] Figure 1 The flow chart of f-BNNS@C-BN / PMMA thermal conductive composite material provided in the above embodiment 1.

[0088] Figure 2 The scanning electron microscope planar view of h-BN (a), BNNS (b) and v-IL@BNNS (c) fillers obtained in embodiment 1 of the application can be seen that the unpeeled h-BN, the sheets are stacked together to present a stacking structure, and the treated BNNS has less sheet stacking and relatively complete size.

[0089] Figure 3 The scanning electron microscope cross-sectional view of f-BNNS@C-BN / PMMA composite material obtained in embodiment 1 of the application can be seen that the composite material has obvious orientation structure, wherein (a) and (b) are different magnifications.

[0090] Figure 4 The horizontal and vertical thermal conductivity coefficient chart of samples obtained in embodiment 1 and comparative examples 1 and 2 of the application can be seen that when the corresponding f-BNNS@C-BN / PMMA composite material, the in-plane and out-of-plane thermal conductivities reach 0.45 W / (mK) and 1.20 W / (mK) respectively, and the thermal conduction enhancement efficiency relative to pure PMMA reaches 221.40% and 252.94% respectively.

[0091] Figure 5 For the compression strain curve and tensile stress-strain curve of the samples obtained in Example 1 and Comparative Example 1 of the present application, it can be seen that the composite material after functional modification exhibits excellent tensile strength, which can reach 35.60 MPa. When the same strain is applied (50%), the compression stress of BNNS@C-BN / PMMA is 67.30 MPa, while the functionalized f-BNNS@C-BN / PMMA can reach 100.30 MPa of compression stress, and the compression strength is significantly improved. At the same time, the functional modification also promotes the uniform dispersion of the filler in the matrix, reduces the stress concentration phenomenon, and significantly enhances the mechanical properties of the composite material.

[0092] Figure 6 For the physical map of the collapsed skeleton obtained in Example 2 of the present application, it can be seen that the formula of the foam template and the process of sintering the three-dimensional skeleton will affect the stability of the skeleton. If not properly controlled, the skeleton will collapse during sintering and cannot form a uniform porous structure.

[0093] Figure 7 For the physical map of the conversion rate less than 10% obtained in Example 3 of the present application, it can be seen that when the conversion rate is too low, the PMMA composite sample will appear delamination during the curing process.

[0094] Figure 8 For the scanning electron microscope images of BN / PUF with different BN contents in Example 3. Within a certain range, BN particles can enhance the nucleation activity, resulting in an increase in the number of pores in a specific area. Through the in-situ polymerization foaming process, BN can be orderly distributed in the polyurethane foam skeleton, but excessive BN will destroy the uniformity and integrity of the cell size, so its addition amount should not be too much.

[0095] The above are only exemplary embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A bulk polymerization method for preparing a PMMA thermally conductive composite material based on a three-dimensional heterojunction thermally conductive skeleton C-BN, characterized by: Firstly, a BN / PUF foam sacrificial template with appropriate pore size and uniform distribution was prepared by in-situ polymerization foaming process, and then a three-dimensional skeleton C-BN was formed by high-temperature carbonization. Then, the three-dimensional thermal conductive skeleton was functionalized with 1-vinyl-3-methylimidazolium iodide and infused with v-IL@BNNS / PMMA prepolymer solution. The f-BNNS@C-BN / PMMA thermal conductive composite material with a low thermal resistance interface structure was prepared by in-situ polymerization.

2. The preparation method according to claim 1, wherein The steps include: Step 1: Preparation of modified C-BN three-dimensional porous thermal conductive skeleton 1a. Add h-BN to polyurethane material A and stir until the h-BN is evenly mixed. Then quickly add material B to the mixture, stir evenly, and let it stand for foaming. This is recorded as BN / PUF foam composite material; 1b. Cut the BN / PUF foam composite material into the required size, place it in a ceramic ark, place it in a tube furnace, and heat it to fully carbonize the polyurethane foam to form a C-BN three-dimensional porous heterojunction thermal conductive skeleton; 1c. Heating the 1-vinyl-3-methylimidazolium iodide ionic liquid to a molten state, and then suspending the C-BN three-dimensional porous heterojunction thermal conductive skeleton and immersing it in the molten ionic liquid to obtain an ionic liquid-modified C-BN three-dimensional porous heterojunction thermal conductive skeleton; Step 2: Preparation of modified BNNS 2a. h-BN powder, zirconia ball milling beads, and deionized water were mixed and ultrasonicated at room temperature. The mixture was centrifuged at 3000 rpm for 10 minutes, the upper liquid layer was collected, and the mixture was centrifuged at 12000 rpm for 10 minutes. The lower solid layer was collected and dried to obtain boron nitride nanosheets. 2b. Add boron nitride nanosheets to an ionic liquid aqueous solution and stir ultrasonically for 12 h. The mixture is ball-milled, filtered, and freeze-dried to obtain ionic liquid-modified BNNS powder. Step 3: Preparation of f-BNNS@C-BN / PMMA thermal conductive composites The ionic liquid modified BNNS powder was added to THF and stirred ultrasonically until uniformly dispersed; the monomer MMA, initiator AIBN and ionic liquid modified BNNS powder were fully mixed and prepolymerized at 80°C under magnetic stirring. When the viscosity of the reaction system became glycerol-like, heating was stopped; the above prepolymer solution was cooled and allowed to stand, and then slowly added dropwise to the modified C-BN three-dimensional porous heterojunction thermal conductive skeleton obtained in step 1; the sample infused with the prepolymer solution was placed in an oven and gradually heated until hardened. After hardening, the temperature was raised to 100-110°C and matured for 1 hour to obtain the f-BNNS@C-BN / PMMA thermal conductive composite material.

3. The preparation method according to claim 2, wherein: In step 1a, the polyurethane material A includes the following components in parts by mass: 73.9 parts of polyether polyol 330N, 8 parts of ethylene glycol, 10 parts of combined polyol POP36 / 28, 1 part of amine catalyst, 0.8 parts of water, 6 parts of HFC-245fa foaming agent, and 0.3 parts of DC-3043 silicone oil; the material B is 48.2 parts of polymethylene polyisocyanate.

4. The preparation method according to claim 2, wherein: In step 1a, h-BN accounts for 2-15 wt% of the total mass of material A and material B.

5. The preparation method according to claim 2, wherein: In step 1b, the carbonization is carried out in an argon atmosphere, with the temperature being raised to 800° C. at a heating rate of 5° C. / min and kept at that temperature for 60 minutes.

6. The preparation method according to claim 2, wherein: In step 2b, the concentration of the ionic liquid aqueous solution is 2-8 wt%.

7. The preparation method according to claim 6, characterized in that: The ionic liquid is one or more of 1-vinyl-3-methylimidazolium iodide, 1-vinyl-3-butylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium chloride, dimethylaminoethyl methacrylate quaternary ammonium salt, and acryloyloxyethyl trimethylammonium chloride.

8. The preparation method according to claim 2, wherein: In step 3, the mass of the ionic liquid-modified BNNS powder accounts for 0.5-5 wt % of the mass of the MMA monomer.

9. The preparation method according to claim 2, wherein: In step 3, the prepolymerization reaction is carried out until the viscosity of the reaction system is 900-1500 mPa·s, and then heating is stopped.

10. A PMMA thermally conductive composite material based on a three-dimensional heterojunction thermally conductive skeleton C-BN, prepared by the preparation method according to any one of claims 1 to 9.